APLIKASI ANALISIS FAKTOR DENGAN MENGGUNAKAN PRINCIPAL COMPONENT AND BERTLETT’S TEST OF SPHERICITY (STUDI KASUS PROSES PENDIDIKAN DI STIA-LAN BANDUNG) - Budi Setiawan1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2005)
Essentially, factor analysis is used for data reduction, i.e. a process to condense plentiful variables into a fewer number called as factor. For example, out of 26 attributes examined to measure students’ attitudes, only several factors can be employed after applying the factor analysis. In this case, 4 variables become the main factor considered to influence the students’ perception. The 4 variables are Cost, Image, Service Encounters, and Evidence of Services. The four variables are, then, to be investigated so that a picture concerning students’ preference toward learning process transpires